Motor cortex tDCS does not modulate perceived exertion within multiple-sets of resistance exercises - Montenegro, R. A.; Farinatti, P. T.V.; de Lima, P. F.M.; Okano, A. H.; Meneses, A. L.; de Oliveira-Neto, L.; Cavalcante, B. R.; de A. Correia, M.; Fontes, E B.; Ritti-Dias, R. M. (Isokinetics and Exercise Science, 2016)
BACKGROUND: Recent evidences have shown that the motor cortex (MC) may influence the rating of perceived exertion (RPE). Given the potential role of transcranial direct current stimulation (tDCS) in modulate cortical areas related to exercise performance, it is possible that tDCS applied on motor cortex (MC) could also influence the RPE during resistance exercises. Recent evidences have shown that the motor cortex (MC) may influence the rating of perceived exertion (RPE). Given the potential role of transcranial direct current stimulation (tDCS) in modulate cortical areas related to exercise performance, it is possible that tDCS applied on motor cortex (MC) could also influence the RPE during resistance exercises. OBJECTIVE: This study analyzed the effects of transcranial direct current stimulation on the rating of perceived exertion during multiple sets of resistance exercises. This study analyzed the effects of transcranial direct current stimulation on the rating of perceived exertion during multiple sets of resistance exercises. METHODS: Thirteen strength-trained men performed a resistance exercise session after either anodal tDCS or sham stimulation applied over the primary motor cortex. Resistance exercise sessions included 3 sets of 10 repetitions of 6 exercises performed with load of at 85% of 8-12 RM. The RPE was obtained using OMNI-Resistance exercise scale. Thirteen strength-trained men performed a resistance exercise session after either anodal tDCS or sham stimulation applied over the primary motor cortex. Resistance exercise sessions included 3 sets of 10 repetitions of 6 exercises performed with load of at 85% of 8-12 RM. The RPE was obtained using OMNI-Resistance exercise scale. RESULTS: The RPE assessed at the end of the sessions was similar in tDCS vs. sham condition (6.78 ± 1.48 vs. 6.87 ± 1.49, respectively; p = 0.56). The RPE for each exercise was similar across conditions, except for the second set of bench press (p = 0.04) and first set of seated-row (p = 0.03). The RPE assessed at the end of the sessions was similar in tDCS vs. sham condition (6.78 ± 1.48 vs. 6.87 ± 1.49, respectively; p = 0.56). The RPE for each exercise was similar across conditions, except for the second set of bench press (p = 0.04) and first set of seated-row (p = 0.03). CONCLUSION: In conclusion, the RPE during multiple sets of submaximal exercises was not modulated by tDCS applied upon MC. In conclusion, the RPE during multiple sets of submaximal exercises was not modulated by tDCS applied upon MC.